Development and Performance of Online Deplasticizer for Accompanying Hangers - LU Guojian, LI Zhijun, WANG Aixiang, ZHAO Jiale (Cailiao Baohu)
To meet the process and performance requirements for online deplasticization of accompanying hangers， a novel， highly efficient deplasticizer was developed.This agent， composed primarily of benzyl alcohol and benzaldehyde as the main solvents， ethylene glycol and ethers as co-solvents， and organic and inorganic bases as promoters， was studied.The factors affecting the deplasticization performance were examined， and the parameter range for the online deplasticization process was determined.The processes and mechanisms of deplasticization at different stages were also discussed.Results showed that under ultrasonic conditions (frequency of 40 kHz)， the time required for complete removal of the plastic powder coating (thickness of 60～70 μm) was found to be less than 3 minutes at 60～75 ℃and a promoter concentration of 2.1～3.3 g/L.The deplasticizer showed low volatility and low corrosiveness to sheet metal， and the solvent was recyclable and regenerable.The polymer network structure of the plastic powder coating was disassembled，and the coating was dispersed or dissolved layer by layer to completely remove the plastic coating.It was deemed suitable for the application scenario of online deplasticization of accompanying hangers.